Mechanical thrombectomy in nonagenarians with acute ischemic stroke. (27th April 2019) - Meyer, Lukas; Alexandrou, Maria; Leischner, Hannes; Flottmann, Fabian; Deb-Chatterji, Milani; Abdullayev, Nuran; Maus, Volker; Politi, Maria; Roth, Christian; Kastrup, Andreas; Thomalla, Goetz; Mpotsaris, Anastasios; et al.
Abstract : Background: Mechanical thrombectomy (MT) is a safe and effective therapy for ischemic stroke. Nevertheless, very elderly patients aged ≥90 years were either excluded or under-represented in previous trials. It remains uncertain whether MT is warranted for this population or whether there should be an upper age limit. Methods: We retrospectively reviewed 79 patients with stroke aged ≥90 years from three neurointerventional centers who underwent MT between 2013 and 2017. Good functional outcome was defined as modified Rankin scale (mRS) ≤2 and assessed at 90-day follow-up. Successful recanalization was graded by Thrombolysis in Cerebral Infarction Scale (TICI) ≥2 b. Feasibility and safety assessments included unsuccessful recanalization attempts (TICI 0), time from groin puncture to recanalization, symptomatic intracranial hemorrhage (sICH), mortality, and intervention-related serious adverse events. Results: Only occlusions within the anterior circulation were included. Median time from groin puncture to recanalization was 39 min (IQR 25–57 min). The rate of successful recanalization (TICI ≥2 b) was 69.6% (55/79). Good functional outcome (mRS ≤2) at 90 days was observed in 16% (12/75) of patients. In-hospital mortality was 29.1% (23/79) and increased significantly at 90 days (46.7%, 35/75; p<0.001). sICH occurred in 5.1% (4/79) of patients. No independent predictor for good functional outcome (mRS ≤2) at 90 days was identified through logistic regression analysis. Conclusion: MT in nonagenarians leads to high mortality rates and less frequently good functional outcome compared with younger patient cohorts in previous large randomized trials. However, MT appears to be safe and beneficial for a certain number of very elderly patients and therefore should generally not be withheld from nonagenarians.